Rare and common species contribute disproportionately to the functional variation within tropical forests - Zhang, S.; Zang, R.; Sheil, D. (Elsevier, 2022)
Understanding how functional traits and functional entities (FEs, i.e., unique combinations of functional traits) are distributed within plant communities can contribute to the understanding of vegetation properties and changes in species composition. We utilized investigation data on woody plants (including trees, shrubs and lianas) from 17 1-ha plots across six old-growth tropical forest types on Hainan island, China. Plant species were categorized as common (>1 individuals/ha) and rare species (≤1 individuals/ha) according to their abundance to determine how they contributed to different ecosystem functions. First, we assessed the differences in traits between common and rare species, and second, we examined functional redundancy, functional over-redundancy, and functional vulnerability for common and rare species of the forests. We found that both common species and rare species in each of the forest types were placed into just a few FEs, leading to functional over-redundancy and resulting in functional vulnerability. Rare species tended to have different trait values than those of common species, and were differently distributed among FEs, indicating different contributions to ecosystem functioning. Our results highlighted the disproportionate contribution of rare species in all of the studied forests. Rare species are more likely than common species to possess unique FEs, and thus, they have a disproportionately large contribution to community trait space. The loss of such species may impact the functioning, redundancy, and resilience of tropical forests.